1994
DOI: 10.1002/cyto.990150405
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of fixatives in high resolution nuclear image analysis

Abstract: Three different methods of fixation (ethanol/Carbowax, formaldehyde, and Carnoy) and four different protocols (without Böhm post‐fixation on an uncoated slide, and with Böhm post‐fixation on Poly‐L‐Lysine coated slide, an uncoated slide and a previously Papanicolaou stained slide) were evaluated for their application in high resolution image analysis of Feulgen stained nuclei. The aim of the study was to find a combination with the best reproducibility and the least variance under normal laboratory conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Pereira et al (2015) described Carnoy as an excellent choice for preservation of both animal and human tissue and demonstrated that this fixative can be used for immunohistochemistry. This fact is possible because of Carnoy's formulation, which contains ethanol, acetic acid and chloroform, generating a great conservative potential for conservation of mammalian tissues (MAKKUS et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al (2015) described Carnoy as an excellent choice for preservation of both animal and human tissue and demonstrated that this fixative can be used for immunohistochemistry. This fact is possible because of Carnoy's formulation, which contains ethanol, acetic acid and chloroform, generating a great conservative potential for conservation of mammalian tissues (MAKKUS et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend using both GLT auto and HT1 auto for image analysis because this was the only combination that yielded equal or better accuracy and reproducibility of PCNA and BrdUrd LI as visual analysis. As suggested by others, optimal sample preparation is critical for accurate image analysis results (7,8,13). Ensuring that labeled cells are clearly differentiated from unlabeled cells through dark and complete immunohistochemical staining is likely to further improve the inter-day and inter-investigator variation in LI IA because the effect of MPB on LI IA will be reduced, leaving one parameter, i.e., size range, as the primary source of inter-day and inter-investigator variation.…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain the accuracy of image analysis results, we recommend optimizing tissue preparation and staining procedures to achieve high quality images free of non-cellular material, and with dark DAB staining and light to moderate hematoxylin staining uniform throughout the sample. As shown in previous studies (16,17,23), for best image analysis results, the fixative should maintain cellular detail, sections should be thin (4-5 µm) to minimize overlapping nuclei, carefully prepared to avoid shredding and wrinkling, and the staining procedures should be optimized to minimize background.…”
Section: Comparison Of Visual and Image Analysismentioning
confidence: 99%